THE INFLUENCE OF HUMATES ON PRO-OXIDANT-ANTIOXIDANT HOMEOSTASIS IN BREEDING BOARS DURING HEAT STRESS - Shostya, M. A.; Pavlova, I. V.; Chukhlib, Ye. V.; Kuzmenko, L. M.; Kodak , T. S.; Bereznytskyi, V. I.; Shaferivskyi , B. S. (Scientific Progress & Innovations, 2020)
In current conditions, in the face of sharp climate change, the introduction of intensive technologies with using biologically active additives aimed at revealing the organism adaptive properties under the action of heat stresses is the main factor of increasing animal productivity. The aim of the study was to determine the influence of substances of humic nature on pro-oxidant-antioxidant homeostasis in the blood of breeding boars of different breeds during heat stress. Adult breeding boars of two breeds were used in the experiment: Poltava Meat (PM) and Red-White Belted Meat (BRWM) breeds, of the same age, live weight and quality of sperm production, which were fed the “Humilid” biologically active feed additive during heat stress. The effect of humic substances on pro-oxidant-antioxidant homeostasis in the blood of breeding boars of different breeds during the period of heat stress was studied. In such case homeostasis was characterized by acceler- ating the processes of peroxide oxidation. The BRWM breed had a negative effect during up to 30 days of the experiment, with further development of the adaptation response. Such changes were accompanied by a de- crease in the activity of superoxide dismutase in PM (p <0.05) and BRWM (p <0.01), the content of reduced glutathione and ascorbic acid with a parallel increase in catalase activity. Different effect of heat stress on the formation of pro-oxidant-antioxidant homeostasis in the blood of different breeds’ breeding boars was revealed. It was determined that the system of generating reactive oxygen forms (xanthine oxidase activity) and their inactivation (superoxide dismutase activity) has a significantly higher functional activity (p <0.05… 0.001) in PM breeding boars as compared with BRWM breeds. Additional feeding of the “Humilid” feed additive to the breeding boars during the period of heat stress contributed to reducing the intensity of peroxidation processes, which was accompanied by accumulating the content of reduced glutathione and ascorbic acid with a parallel decrease in the concentration of dehydroascorbic acid. The existence of inter- breed difference to the effect of the “Humilid” feed additive was recorded. Thus, a more effective action of the feed additive was registered in BRWM as compared with PM breed, which was manifested by a rapid recovery of glutathione, ascorbic acid, as well as a decrease in diene conjugates and TBA-active complexes, indicating earlier activation of the organism's adaptation processes in the first genotype under the condition of heat stress.